Krüppel-Like Factor 12 Promotes Colorectal Cancer Growth through Early Growth Response Protein 1 - Kim, Sun-Hee; Park, Yun-Yong; Cho, Sung-Nam; Margalit, Ofer; Wang, Dingzhi; DuBois, Raymond N. (PLOS ONE, 2016)
Krüppel-like factor 12 (KLF12) is a transcription factor that plays a role in normal kidney development and repression of decidualization. KLF12 is frequently elevated in esophageal adenocarcinoma and has been reported to promote gastric cancer progression. Here, we examined the role of KLF12 in colorectal cancer (CRC). Indeed, KLF12 promotes tumor growth by directly activating early growth response protein 1 (EGR1). The levels of KLF12 and EGR1 correlate synergistically with a poor prognosis. These results indicate that KLF12 likely plays an important role in CRC and could serve as a potential prognostic marker and therapeutic target.